EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) SEBAGAI ANTINEFROTOKSISITAS BERDASARKAN PENURUNAN KADAR KREATININ TIKUS - Sukmawati Sukmawati; Ira Asmaliani (As-Syifaa Jurnal Farmasi, 2019)
Nephrotoxicity is a disorder of the kidneys that occurs when exposed to drugs or toxins. Pandan wangi leaves have antioxidant activity expected to give antinephrotoxicity effect. This aim of study is to determine the antinephrotoxicity effect of the ethanol extract of pandan wangi leaves (Pandanus amaryllifolius Roxb.) based on the decline of rat creatinine level induced by gentamicin. Eighteen male Wistar rats were divided into 6 groups. That is naive, negative control by Na-CMC 1%, positive control by the suspension of keto acids, and treatment group with ethanol extract of pandan wangi leaves at 125 mg/kgBW, 250 mg/kgBW and 500 mg/kgBW. Nephrotoxicity condition was induced by Gentamicin 80 mg/kgBW (ip) for seven days. The blood samples were taken and measured the serum creatinine levels on days 0, 8th and 22th by Human Analyzer. The results study showed that ethanol extract of pandan wangi leaves at 250 mg/kgBW and 500 mg/kgBW have the effect as antinephrotoxicity based on decreased creatinine levels.